An Appraisal of One-Year Online B.ED. Program in Nepal: A Case of Nepal Open University - Oli, Indra Kumari; Tiwari, Yasoda (Journal of NELTA Karnali, 2024)
This study aimed to evaluate the effectiveness of a one-year B.Ed. program given via online mode at Nepal Open University (NOU). This study focused on thoroughly evaluating a one-year B.Ed. in the English specialization program through Stufflebeam’s CIPP evaluation model. The program was examined and evaluated from the perspectives of the facilitators and the student teachers who had experienced it via online modality. They were two lecturers who taught the English specializing course in a one-year B.Ed. Program at Nepal Open University and two students who studied and completed this program at the same university in 2022. The data were collected through the semi-structured interview based on the CIPP evaluation checklist and analyzed thematically. There was a low enrollment of the students in the beginning phase however, it attracted many students later. The teacher students and course facilitators agreed the program was a bridge between a non-teacher education program and a teacher education program. However, some contradictory views between teacher- students, and facilitators were also explored. The facilitators expressed that one- year time was not enough for the course whereas the students were happy with the time specified for the course.